Treatment of Axillary hyperhidrosis. (20th August 2021) - Arora, Gulhima; Kassir, Martin; Patil, Anant; Sadeghi, Payam; Gold, Michael H.; Adatto, Maurice; Grabbe, Stephan; Goldust, Mohamad
Abstract: Background: Axillary hyperhidrosis characterized by excessive sweating in the axillary regions is a frustrating chronic autonomic disorder leading to social embarrassment, impaired quality of life and usually associated with palmoplantar hyperhidrosis. Identifying the condition and its cause is central to the management. Aim: The aim of this article is to discuss treatment options for axillary hyperhidrosis. Methods: Comprehensive literature search using PubMed and Google Scholar was performed to review relevant published articles related to diagnosis and treatment of axillary hyperhidrosis. Results: Treatment modalities for axillary hyperhydrosis vary from topical and systemic agents to injectables, newer devices and surgical measures. None except for physical measures using devices or surgery, which destroys the sweat glands to remove them, is possibly permanent and most are associated with attendant side effects. Conclusion: Several treatments including medical and surgical option are available for the treatment of axillary hyperhydrosis. Patient education is important component of its management. Individualized approach of management is necessary for optimal outcome of treatment.